EVALUATION OF LEGAL AND SOCIAL RESPONSIBILITY: THE CASE OF FUTURE POLICE OFFICERS - Nedzinskienė, Rūta; Nedzinskas, Egidijus (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Changes in today’s global political, economic, demographic and cultural situation make the relations in society to get sophisticated. Legal and social responsibility becomes critical important in these processes. Because of their professional duties, police officers must be professionals with a very high level of responsibility. However, there is a lack of scientific researches with a particular reference to future police officers responsibility evaluation. This leads to the aim of this research: to evaluate legal and social responsibility of future police officers. The research was based on systematic and comparative scientific literature analysis and statistical data analysis. The study was conducted in 2011 and 2015 in one of Lithuanian universities. 102 recipients of the study program “Law and Police Activities” participated in the survey in 2011 and 109 – in 2015. It was found that students – future police officers feel legal as well as social responsibility. Although the greatest impact on the formation of respondents' responsibility had a family, the relevance of the university‘s contribution has grown from 2011 to 2015. It is also to notice that 66 % of respondents marked that they are legal responsible in 2011 and this proportion increased to 82 % in 2015. The obtained results will contribute in further investigations making analysis of future professionals’ responsibility and its factors.